2013
DOI: 10.1007/s10560-013-0305-5
|View full text |Cite
|
Sign up to set email alerts
|

The Sense of School Belonging and Implementation of a Prevention Program: Toward Healthier Interpersonal Relationships Among Early Adolescents

Abstract: The purpose of this qualitative study is to pave the way for the establishment of healthy interpersonal relations by facilitating an understanding of the impacts of Lions Quest Skills for Adolescence as perceived by adolescents and teachers who took part in it. Lions Quest has become recognized as an evidence-based program for preventing alcohol and drug use through the development of social skills and the promotion of meaningful engagement in the school community (Lions Clubs International, Overview of Skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Having a positive sense of belonging has been found to enhance interpersonal, professional and academic success, improve self-concept, to be a protective factor for suicide and overall to be vital to psychological functioning (Brown, Silvia, Myin-Germeys, & Kwapil, 2007; Drolet, Arcand, Ducharme, & Leblanc, 2013; Hagerty, Williams, Coyne, & Early, 1996; Kissane & McLaren, 2006). The data underscore that meaningful connections and presence of others in the lives of persons with schizophrenia can impact well-being and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…Having a positive sense of belonging has been found to enhance interpersonal, professional and academic success, improve self-concept, to be a protective factor for suicide and overall to be vital to psychological functioning (Brown, Silvia, Myin-Germeys, & Kwapil, 2007; Drolet, Arcand, Ducharme, & Leblanc, 2013; Hagerty, Williams, Coyne, & Early, 1996; Kissane & McLaren, 2006). The data underscore that meaningful connections and presence of others in the lives of persons with schizophrenia can impact well-being and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, our study points out that family communication, academic performance, school attachment and violent behaviours are possible areas for family and school-based health-promoting interventions. Other studies have demonstrated that interventions promoting positive interactions and effective communication between family members and between teachers and students help to develop a sense of belonging to families, schools, and communities and may promote healthier behaviours in adolescence [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some studies have highlighted the benefit of using programs that help to develop constructive commitment and sense of belonging to families, schools, and communities. This is performed through the development of social skills and competences that allow them to communicate effectively, make better decisions, build better self-esteem, and have a greater sense of personal responsibility ( 48 , 49 ). Additionally, interventions that promote positive relationships between teachers and students and a sense of belonging may also help to promote other healthy behaviors ( 50 ).…”
Section: Discussionmentioning
confidence: 99%